Digitalisasi Pembelajaran: Pengaruh Edugame Terhadap Kemampuan Berfikir Kritis Siswa - Slamet Sariyanto; Iswahyudi Joko Supriyitno; Dwi Sulistyaningsih (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study discusses the effect of using digital-based educational game learning media on critical thinking skills at elementary and junior high school levels with a focus on mathematics subjects. The aim is to find out whether the learning media used has an impact on students in improving critical thinking skills. The method in this study is the systematic literature review (SLR) method. This method is carried out by reviewing articles from Google Scholar and Knowledge Maps sources from the years of publication 2020-2024. The review process consists of 3 stages, namely planning, conducting and reporting, the results and conclusions obtained regarding the use of educational game media on critical thinking skills have increased in use from year to year, especially in quiz-based games, while storytelling-based games are still rarely studied in their use. The use of educational games in research that has been conducted has shown an influence in improving students critical thingking skills.